The Effect of Zinc on the Structural, Electrical, and Mechanical Properties of YBCO-123 Superconducting Nanoparticles Prepared by an Acetate-Based Sol-Gel Process - Asikuzun, E.; Ozturk, O.; Aydemir, G. A.; Tasci, A. T. (Springer Science and Business Media LLC, 2019)
In this study, zinc (Zn)-doped YBaCuO (YBCO)-123-based high-temperature superconducting samples were produced using the sol-gel method, which is commonly used for preparing nanosize materials. Zn ions were substituted by Cu ions (YBa2Cu3-xZnxO), and Zn doping effects on structural, electrical, and mechanical properties of the YBCO-123 superconductors were examined in detail. Undoped sample was prepared under same conditions. X-ray diffraction analysis (XRD) was used to determine phase analysis and lattice parameters of the superconducting samples. To analyze the microstructure properties, scanning electron microscope (SEM) measurements were performed. Resistivity and microhardness measurements were also carried out for superconducting and mechanic properties, respectively. Vickers microhardness, young modulus, fracture toughness, and yield strength values of the samples were calculated. Microhardness measurements were analyzed using the Kick’s law, proportional sample resistance (PSR) model, EPD model, the Hays-Kendall (HK) approach, and indentation-induced cracking (IIC) model.